A Brief Insight into the Introduction of a New Tax Regime in India - Ojha, Shalini; Agarwala, Amal Kumar (International Journal of Economics and Financial Issues, 2024)
Since the inception of a new regime for filing taxes, there has been a discourse among taxpayers. The old tax regime provides opportunities to save taxes while, building a portfolio for fulfilling their financial goals. After the introduction of the new tax regime with less exemptions and deductions, one is free to choose between any of the two regimes. This would depend on many factors but purely on the quantum of exemptions and deduction one hopes to avail. For individuals, with awareness about their financial condition for the year, choices are clear. Otherwise, it may end in a deadlock. A commentary on the tax regimes could be an added factor in the selection. However, due to unavailability of the acceptance rate for new tax regime, taxpayers are unable to gauge whether the new tax regime is favourable. Amidst this, the finance minister has made some vivid introductions to the new tax regime in the union budget of 2023 by increasing the tax rebate limit. This introduction is a valuable step for the tax system of India which has the potential to be advantageous for taxpayers. Hence, this research is conducted to understand the new tax regime and the role it can play for the welfare of taxpayers. This study also sheds some light on the factors which might influence the selection of the tax regime. The findings show that the new tax regime simplifies the decision structure available to the taxpayers by reducing complexity and increasing the ease of compliance. The acceptance of the new tax regime has also increased since the reforms introduced in the Union budget of 2023. Age Groups, Yearly Income and Number of investments are factors that influence the selection of the tax regime. It is also observed that the younger age groups are inclining towards the new tax regime. The collected data has been analysed using the Year over Year growth, Chi-Square test and One-way ANOVA test along with post hoc tests.